2010
DOI: 10.1002/pros.21276
|View full text |Cite
|
Sign up to set email alerts
|

Androgen regulation of micro‐RNAs in prostate cancer

Abstract: BACKGROUND Androgens play a critical role in the growth of both androgen dependent and castration‐resistant prostate cancer (CRPC). Only a few micro‐RNAs (miRNAs) have been suggested to be androgen regulated. We aim to identify androgen regulated miRNAs. METHODS We utilized LNCaP derived model, we have established, and which overexpresses the androgen receptor (AR), the VCaP cell line, and 13 intact‐castrated prostate cancer (PC) xenograft pairs, as well as clinical specimens of untreated (PC) and CRPC. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
126
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 47 publications
(77 reference statements)
4
126
1
2
Order By: Relevance
“…In the patient cohort presented in this study, the expression of the diagnostic and prognostic miR-221/222 is strongly downregulated during disease progression. Similar downregulation was observed for PCa cell lines (Waltering et al, 2011). In the latest study, only four miRNAs showed similar regulation in both, cell lines and xenograftpairs, and only miR-141 demonstrated concordant expression in castration resistant PCa clinical specimens when compared with PCa.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the patient cohort presented in this study, the expression of the diagnostic and prognostic miR-221/222 is strongly downregulated during disease progression. Similar downregulation was observed for PCa cell lines (Waltering et al, 2011). In the latest study, only four miRNAs showed similar regulation in both, cell lines and xenograftpairs, and only miR-141 demonstrated concordant expression in castration resistant PCa clinical specimens when compared with PCa.…”
Section: Discussionsupporting
confidence: 67%
“…For example, it has been shown that elevated expression of miR-21 can enhance PCa tumor growth in vivo and, is sufficient for androgen-dependent tumors to overcome castration-mediated growth arrest (Ribas et al, 2009). We recently identified miR-21 together with miR-32, miR-141, miR-221 and miR-375 as differentially expressed during dihydrotestosterone stimulation of different PCa cell lines or 13 intact-castrated pairs of PCaxenografts (Waltering et al, 2011). It has been reported that the mir-221/222 cluster is upregulated in matched androgen-dependent and androgen-independent PCa cell lines (Sun et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For hsa-miR-141 and hsamiR-375, this finding is consistent with previous studies. 40,41 We propose that these miRNAs are expressed in prostate cancer cells and released into surrounding blood vessels during disease progression. Interestingly, hsa-miR-346 was elevated in the serum of men with mCRPC but reduced in metastases in the MSKCC cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the miRNA transcriptome is profoundly affected by androgen signaling in PCa (for review, see Coppola et al (2009)), it is not surprising that androgenic regulation of many of the circulating miRNAs described earlier has been documented (e.g. miR-141 and other miR-200 family members (Szczyrba et al 2010, Waltering et al 2010, miR-375 (Szczyrba et al 2010, Waltering et al 2010, miR-21 (Shi et al 2007, Ribas et al 2009, Narayanan et al 2010, and miR-221 (Sun et al 2009)). These observations provide important mechanistic information regarding the origins of these potential biomarkers, which may be critical for their effective clinical implementation.…”
Section: Association Between Androgen Signaling and Circulating Mirnamentioning
confidence: 99%